Generalized Relaxation Behavior of Rock Under Various Loading Conditions Using a Constant Linear Combination of Stress and Strain - Zhang, Hailong; Tang, Yang; Okubo, Seisuke; Peng, Shoujian; Chen, Cancan (Frontiers in Earth Science, 2021)
Time-dependent behavior has been demonstrated to be an essential factor in determining the long-term stability of underground structures. Creep and relaxation experiments are commonly used to investigate time-dependent behavior by subjecting rock to constant stress and strain. However, both stress and strain of in-situ rock masses are likely to change with time, a phenomenon known as generalized relaxation that has not been thoroughly investigated. In this study, a newly proposed control method with a constant linear combination of stress and strain as a feedback signal is used in compression and tension tests to investigate generalized relaxation behaviors of rocks. The results showed that the stress and strain of generalized relaxation are dependent on values of α, which represented generalized relaxation direction. The isochronous curves are enclosed within stress–strain curves of different loading conditions. The variation of stress (∆σ) and strain (∆ε) increases with increasing stress level and decreases with increasing confining pressure. Also, ∆σ and ∆ε in region II are smaller than in regions I and III. Furthermore, by performing brittle rock tests, complete generalized relaxation curves are obtained; three stages are observed, which are similar to conventional creep and relaxation behavior. Finally, the time and generalized relaxation failure behavior of Class I and Class II rock are discussed. The study is a valuable resource for gaining a comprehensive understanding of the time-dependent behavior of rocks and improving the stability and safety of underground structures.